2016
DOI: 10.1111/bjd.14308
|View full text |Cite
|
Sign up to set email alerts
|

Mohs micrographic surgery for basal cell carcinoma: evaluation of the indication criteria and predictive factors for extensive subclinical spread

Abstract: We found that tumour size and aggressive histology are the strongest indication criteria for MMS. Recurrence and aggressive histology are predictors for extensive subclinical spread but not for two or more rounds of MMS. Evidence-based indications for MMS are necessary to ensure cost-effective management of BCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
2
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 19 publications
(18 reference statements)
2
41
2
11
Order By: Relevance
“…In particular, microscopically controlled surgery is indicated for tumors associated with an increased likelihood of subclinical spread and recurrence . This includes recurrent tumors with extensive subclinical spread and a likelihood of renewed recurrence between 11.6 and 17.4 % .…”
Section: Risk Stratificationmentioning
confidence: 99%
“…In particular, microscopically controlled surgery is indicated for tumors associated with an increased likelihood of subclinical spread and recurrence . This includes recurrent tumors with extensive subclinical spread and a likelihood of renewed recurrence between 11.6 and 17.4 % .…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Mikroskopisch kontrollierte Chirurgie ist insbesondere bei Tumoren indiziert, die mit einer erhöhten Wahrscheinlichkeit subklinischer Ausläufer und Rezidive einhergehen . Hierzu zählen auch Rezidivtumoren, die ausgedehnte subklinische Ausläufer aufweisen und deren Wahrscheinlichkeit zur Ausbildung erneuter Rezidive zwischen 11,6 und 17,4 % liegt .…”
Section: Chirurgische Therapieunclassified
“…3 In their series of more than 1000 BCCs, only 25% of the tumours were cleared by one single stage of MMS. Hypothetically, only these 25% would have been successfully treated by a 2-mm standard excision.…”
mentioning
confidence: 98%
“…The authors concluded that MMS was the treatment of choice for facial BCCs larger than 1 cm 2 , with a morphoeiform, micronodular or mixed histology. 3 MMS on frozen sections is labour intensive, time-consuming and needs a specialized setting. The authors state that in Belgium, reimbursement, and thus costs for society, for MMS are approximately eight times higher than for standard excision.…”
mentioning
confidence: 99%
See 1 more Smart Citation